Febril Konvülziyon - Türkmen, Dilek (Canpolat, Temel Pediatrik Epilepsi, 2024)
Febril konvülziyon, 6 ay ile 6 yaş arasında görülen, ateşle ilişkili nöbetlerdir. Genellikle iyi huyludur ve uzun vadeli nörolojik komplikasyonlara yol açmaz. Tanı için, 38.3°C'den yüksek ateşle ilişkili nöbetlerin, merkezi sinir sistemi enfeksiyonu veya inflamasyonu olmaması ve konvülsiyona sebep olabilecek akut metabolik bir patolojinin bulunmaması gerekir. Febril konvülziyonlar basit ve komplike olarak ikiye ayrılır. Febril status epileptikus, 30 dakikadan uzun süren nöbetler için kullanılır. Basit febril konvülziyonda tedavi gerekmez. Ebeveynler, evdeki nöbet konusunda ve nöbet tekrarı konusunda eğitilmelidir. Febrile convulsions are seizures that occur in children between the ages of six months and six years. They are typically benign and do not result in long-term neurological complications. The diagnosis requires that the seizures be associated with a temperature higher than 38.3°C, that there be no evidence of central nervous system infection or inflammation, and that there be no acute metabolic pathology that could cause convulsions. Febrile convulsions are divided into two categories: simple and complicated. Febrile status epilepticus is used to describe seizures that last longer than 30 minutes. No treatment is required for simple febrile convulsions. Parents should be educated about seizures at home and the possibility of recurrence.